Improved Masking Multiplication with PRGs and Its Application to Arithmetic Addition - Bohan Wang; Qian Sui; Fanjie Ji; Chun Guo; Weijia Wang (IET Information Security, 2024)
At Eurocrypt 2020, Coron et al. proposed a masking technique allowing the use of random numbers from pseudo-random generators (PRGs) to largely reduce the use of expansive true-random generators (TRNGs). For security against d probes, they describe a construction using 2d PRGs, each of which is fed with at most 2d random variables in a finite field, resulting in a randomness requirement of O∼d2. In this paper, we improve the technique on multiple frontiers. On the theoretical level, we push the limits of the randomness requirement by providing an improved masking multiplication using only d PRGs, each of which is fed with d random variables, saving more than half random bits. On the practical level, considering that the masking of arithmetic addition usually requires more randomness (than multiplication), we apply the technique to the algorithm proposed at FSE 2015 that is a very efficient scheme performing arithmetic addition modulo 2w. It significantly reduces the randomness cost of masked arithmetic addition, and further advocates the advantage of masking with PRGs. Furthermore, we apply our masking scheme to the SPECK, XTEA, and SPARKLE, and provide the first (to the best of our knowledge) higher order masked implementations for the ciphers using ARX structure.